2016
DOI: 10.4103/2229-516x.192593
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of elevated serum testosterone in pathogenesis of renal stone formation

Abstract: Background:Urolithiasis or renal stone formation occurs with three times higher frequency in males and decreases with age in parallel with the serum testosterone levels, suggesting a role played by male sex hormones. Androgens appear a promotion action and estrogens an inhibitory action on kidney stone formation in several animal models suggesting a study to be carried out to deduce the role played by serum testosterone in the formation of renal stones.Aim:The aim of this study is to define the involvement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In the context of our study, male preponderance was observed. It can be attributed to effect of sex hormones on some lithogenic risk factors and concentration of lithogenic factors in the urine which is greater in men than that in women [ 14 – 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of our study, male preponderance was observed. It can be attributed to effect of sex hormones on some lithogenic risk factors and concentration of lithogenic factors in the urine which is greater in men than that in women [ 14 – 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Renal calculi are more prevalent in males and postmenopausal females, indicating the possible role of androgen in renal calculi formation. A significantly higher level of testosterone was reported in those with renal calculi [16,18,19,22]. In Mohammad's study, the testosterone level was 3.3 ng/mL in patients with renal calculi and 2.41 ng/mL in the control group [18].…”
Section: Discussionmentioning
confidence: 86%
“…ADT may alter the risk of renal calculi. A significantly higher level of androgen was observed in patients with renal calculi [16,18,19]. From this viewpoint, ADT may decrease the risk of renal calculi.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, estrogen use may involve in urinary excretion of kidney stone constituents and of urinary promoters. Elevated levels of serum testosterone and serum dihydrotestosterone might be involved in increased incidences of stone formation (Gupta et al, 2016[ 9 ]). In the clinical trials conducted by Maalouf et al (2010[ 11 ]) PMH use is associated with higher risk of kidney stone formation (Maalouf et al, 2010[ 11 ]).…”
Section: Discussionmentioning
confidence: 99%